Implementasi Pengendalian Pemanfaatan Ruang dan Sanksi Administratif Dalam Rencana Tata Ruang Wilayah Kabupaten Sidoarjo - Sugiarto, Agus (JKMP (Jurnal Kebijakan dan Manajemen Publik), 2017)
This research aimed to organize spatial arrangement in accordance with the provisions of the legislation and creating spatial order, there should be efforts to increase supervision and control of spatial utilization of space. There are some instruments that must be observed in control of spatial planning in Sidoarjo. The purpose of this study is to describe and analyzed the implementation of controls spatial use Sidoarjo. Date analysis technique used is descriptive qualitative models. The results showed that of the four (4) instrument control utilization of existing space, only 2 (two) instrument that is implemented by the Government of Sidoarjo regency namely instrument permitting and sanctioning. Implementation of administrative sanctions for violations of the space utilization is merely a written warning, followed by sealing. There are no penalties up to the demolition level of development.